Enhancing Enzyme-Mediated Cellulose Hydrolysis by Incorporating Acid Groups Onto the Lignin During Biomass Pretreatment - Wu, Jie; Chandra, Richard P.; Takada, Masatsugu; Liu, Li-Yang; Renneckar, Scott; Kim, Kwang Ho; Kim, Chang Soo; Saddler, Jack N. (Frontiers in Bioengineering and Biotechnology, 2020)
Lignin is known to limit the enzyme-mediated hydrolysis of biomass by both restricting substrate swelling and binding to the enzymes. Pretreated mechanical pulp (MP) made from Aspen wood chips was incubated with either 16% sodium sulfite or 32% sodium percarbonate to try to incorporate similar amounts of sulfonic and carboxylic acid groups onto the lignin (60mmol/kg substrate) present in the pulp without resulting in significant delignification. When Simon’s stain was used to assess potential enzyme accessibility to the cellulose, it was apparent that both post-treatments enhanced accessibility and cellulose hydrolysis. To try to further elucidate how acid group addition might influence potential enzyme binding to lignin, Protease Treated Lignin (PTL) was isolated from the original and modified mechanical pulps and added to a cellulose rich, delignified Kraft pulp. As anticipated, the PTLs from both the oxidized and sulfonated substrates proved less inhibitory and adsorbed less enzymes than did the PTL derived from the original pulp. Subsequent analyses indicated that both the sulfonated and oxidized lignin samples contained less phenolic hydroxyl groups, resulting in enhanced hydrophilicity and a more negative charge which decreased the non-productive binding of the cellulase enzymes to the lignin.